Global Competitiveness Potential of U.S. Nuclear Energy Technologies - T. V. Voronin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The new Trump administration considers the U.S. nuclear energy industry as one of the most important and promising tools for maintaining the country’s global leadership in the international arena. In order to assess the validity of these calculations, this paper provides a retrospective analysis of the development of U.S. nuclear industry, identifies its strengths and weaknesses and the overall state as D. Trump is about to enter his second term. The first section outlines the key stages and drivers of the U.S. nuclear energy industry evolution in the second half of the 20th century. The author notes that the development of the industry was steadily slowing down after a period of rapid growth in the 1960–1970s due to both purely economic reasons and extraordinary factors, including the accident at the Three Mile Island nuclear power plant. The second section compares the approaches of the administrations of George W. Bush, B. Obama, D. Trump and J. Biden to regulating the national nuclear energy industry. The research shows that, despite active government support of the industry, the trend towards a ‘nuclear renaissance’ emerged only with D. Trump's coming to power, as he set a course to restore the competitiveness of the country’s nuclear industry and establish dominance in this segment of international energy market. The author concludes that the U.S. nuclear energy technologies have significant potential in terms of strengthening the country’s global competitiveness, which, in particular, became possible thanks to the policy of the last two administrations to subsidize and technologically upgrade the nuclear industry, as well as to develop new markets in Europe and Asia. At the same time, as the author notes, there are still certain capacity constraints, related, in particular, to the disposal of spent nuclear fuel and the transition to cost-effective production of small modular reactors.